EFFECTS OF DIFFERENT SUTURE MATERIALS ON TISSUE HEALING - Fırat SELVİ; Sırmahan ÇAKARER; Taylan CAN; Serpil İrem Kirli TOPÇU; Alen PALANCIOĞLU; Başak KESKİN; Bilge BİLGİÇ; Mehmet YALTIRIK; Cengizhan KESKİN (Istanbul University, 2016)
Purpose: The purpose of this study was to investigate the healing differences in between four different widely used suture materials in the oral surgery practice, including silk (Perma- Hand; Ethicon, INC., Somerville, NJ, USA), polypropylene (Prolene; Ethicon, INC., Somerville, NJ, USA), coated polyglactin 910 (Ethicon, INC., Somerville, NJ, USA). and polyglecaprone 25 (Ethicon, INC., Somerville, NJ, USA ). Materials and Methods: 20 male rats were randomly allocated into two groups depending on their sacrification days (post-operative 1st and the 7th days). Four longitudinal incision wounds, each 1cm in size, were created on the dorsum of each animal which were then primarily closed with four different types of sutures. Results: The effects of these suture materials on soft tissue healing were compared histopathologically, by means of density of the cells, necrosis, fibrosis, foreign body reaction, the presence of cells of acute and chronic infection. No statistically significant difference was observed between the groups regarding the density of the cells, necrosis, fibrosis, foreign body reaction, and the presence of the cells of acute & chronic infections. Of note, propylene showed slightly less tissue reaction among the other materials. Conclusion: The results of our study showed that there is no only one ideal suture material for surgical practice. The factors related to the patient, the type of the surgery and the quality of the tissue are important to decide an appropriate suture material.